Comparative study on the influence of initial deformation and temperature of thermally induced white etching layers on rail wheels. (January 2023) - Freisinger, M.; Rojacz, H.; Pichelbauer, K.; Trausmuth, A.; Trummer, G.; Six, K.; Mayrhofer, P.H.
Abstract: Detailed investigations of white etching layers (WELs) formed on rails and wheels are of utmost importance to improve railway safety. This calls for lab-generated WELs with well-comparable characteristics to conduct further testing such as in twin-disc experiments. In this work, laser surface treatments were applied on wheel steels to induce thermally induced WELs. To evaluate the influence of the initial deformation state of the sample, undeformed and severely plastically deformed ER7 wheel steels were selected. In this study, it is shown that surface temperatures of > 640 °C lead to thermally induced WELs, with differences based on the initial deformation state. The thermally induced WELs are compared to a field-WEL present on an ex-service railway wheel. Results indicate that the WEL induced by laser treatment on an initially deformed wheel material provides the best match with the field-WEL. The most distinct difference is a grain size gradient within the outermost 30 µm of the field-WEL caused by deformation after the formation in service. This study clearly shows that the variation in initial microstructures and laser process parameters leads to differences in microstructural characteristics of thermally induced WELs and must be considered when imitating and testing WELs in laboratories.